Angle dependence of planar Hall resistance and anisotropic magnetoresistance of (Ga, Mn)As and Permalloy microdevices - Jung, M. H.; Park, S.; Eom, J.; Chun, S. H.; Shin, K. (AMER INST PHYSICS, 2008)
We present systematic studies on the angle dependence of planar Hall resistance and anisotropic magnetoresistance of ferromagnetic semiconductor (Ga,Mn) As and metallic Permalloy (Py) microdevices. (Ga,Mn) As shows two distinct planar Hall resistance switchings when the magnetic field is applied in the plane, indicating the magnetization reversal by 90 degrees due to the cubic magnetocrystalline anisotropy. Similar magnetization reversal is observed in metallic Py microdevices. The broader planar Hall resistance jump observed in the Py device is attributed to the uniaxial shape anisotropy and complex domain rotation at the voltage probe. Nevertheless the observed planar Hall effect of Py is comparable to that of (Ga, Mn)As. (C) 2008 American Institute of Physics. [DOI: 10.1063/1.3003049]
Keywords: EPITAXIAL FE; WIRE